INEQUALITY ACROSS NURSING HOMES: MEASUREMENT OF RACIAL SEGREGATION AMONG NURSING HOMES IN THE UNITED STATES. (16th November 2018) - Mack, D; Lapane, K
Abstract: Nursing homes are not immune to the residual effects of lawful racial segregation that was previously instituted in the United States. However, a standardized approach to measure segregation in nursing homes does not appear to be established. A systematic review was conducted to identify all formal measurement approaches to evaluate racial segregation among nursing home facilities, and to then identify facility-level associations between segregation and quality of care. PubMed, Scopus and Web of Science databases were searched for studies relating to segregation among nursing homes across the United States. Following the PRISMA guidelines, literature was systematically evaluated and studies were excluded if articles were not in English, were not original, or did not formally measure racial segregation of nursing homes residents with regional-level data. Formal segregation measures identified included the Dissimilarity Index, the Disparities Quality Index, the Modified Thiel's Entropy Index, the Gini coefficient, and adapted models. The most common data sources used were the Minimum Data Set (MDS; resident-level data), the Certification and Survey Provider Enhanced Reporting data (CASPER; facility-level data), and the Area Resource File/ US Census Data (regional-level data). Overall, the measurement of racial segregation among nursing homes is heterogeneous. While there are limitations to each methodology, this review can be used as a reference when trying to determine the best approach to measure racial segregation in future studies. Moreover, most studies showed evidence of racial segregation among nursing home facilities and subsequently, a negative impact of segregation on racial minorities and facility quality outcomes.